The relationship between visceral adipose tissue and osteoarthritis among older adults: evidence from the NHANES 1999–2018 - Huang, Wei; Xiao, Yin-sheng; Zou, Yu-hang; Zhong, Lu-qun; Huang, Gui-qiong (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to assess any possible links between visceral fat accumulation and an elevated prevalence of osteoarthritis (OA) in the elderly.Methods3,779 subjects aged 65 years or older from the National Health and Nutrition Examination Survey (NHANES) 1999–2018 were finally included, of whom 516 had OA. The identification of patients diagnosed with OA was conducted using questionnaire data. The visceral adiposity index (VAI) was computed utilizing body mass index (BMI), waist circumference (WC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C). To investigate the relationship between VAI and OA, weighted multivariable logistic regression analysis, restricted cubic spline (RCS), subgroup analyses, and interaction tests were carried out.ResultsMultivariate logistic regression analysis showed that the increase in VAI is accompanied by an increased prevalence of OA after fully correcting for variables. The top quartile of VAI had a prevalence that was 110% higher than the lowest quartile. A non-linear positive correlation between VAI and OA was found in the RCS.ConclusionThis study suggests a potential correlation between elevated VAI and increased prevalence of OA in older adults, and that lowering VAI may have an impact on the prevalence of OA.